ACCESS TO JUSTICE AND ADMINISTRATION OF LEGAL CONFLICTS: FROM THE SENTENCE CULTURE TO A CONSENSUAL CULTURE - Maillart, Adriana Silva; Soares Stersi dos Santos, Ricardo; Gonçalves, Jéssica (Revista de Direito Brasileira, 2019)
The purpose of this article is to analyze, within the prism of the innovations proposed by the Judiciary Reform, with the creation of CNJ and specific guidelines for the creation of alternative means to the Judiciary, why the sentence culture is perpetuated as a paradigm of resolution of conflicts, to the detriment of the culture of consensus. To do so, we analyze the origin of the conflict, the specificities of the sentence and consensus cultures, and then establish the main obstacles to the substitution of the culture of the sentence by a consensual culture of conflict management. This paper adopts the hypothetical-deductive method of research and the documentary and bibliographic review, as a research technique.